Andanças, movimentos e luta quilombola no Norte de Minas Gerais - Costa, Pedro Henrique Mourthé de Araújo (2021)
This dissertation is an ethnography of the quilombolas – rural black communities – located in the North region of the State of Minas Gerais, their luta [struggle], movements and an-danças [wayfaring]. Following my quilombola research partners in various events and activ-ities in the world of social movements and undertaking visits and stays in communities from 2016 to 2018 allowed me to understand how the quilombola struggle is done in movement, in the circulation of people, knowledge, things, symbols, practices and traditions. In their wayfaring and caminhadas [walks], the quilombolas take their flags, clothing, ornaments, instruments, songs, gritos de ordem [slogan chanting], prayers and batuque [drumming]. All these elements, which circulate and give form to the struggle, define a particular mode of political engagement. The struggle demands a kind of engagement for which movement is central, being related to various kinds of knowledge, acquired and produced through wayfar-ing. Besides its importance to the region's territorial struggles, wayfaring is also immanent to the quilombola way of life in their territories. In this sense, I try to think of wanderings not only as physical displacements between different places. Instead, the idea is to reflect about these and other movements as a unique way of living and acting in the world. Or ra-ther, a way to dwell the worlds among which they circulate in their struggle.